Vacuum arcs and gradient limits - Norem, J.; Moretti, A.; Insepov, Z. (Proceedings of 2011 Particle Accelerator Conference, New York, 2011)
We have been extending and refining our model of vacuum breakdown and gradient limits and describe recent developments. The model considers a large number of mechanisms, but finds that vacuum arcs can be described fairly simply and self-consistently, however simulations of individual mechanisms can be involved, in some cases. Although based on accelerator rf data, we believe our model of vacuum arcs should have general applicability. The paper explores breakdown in plasmas, and self-sputtering and damage by parasitic arcs.
Keywords: vacuum breakdown; gradient limits; rf